PEDAGOGICAL APPROACHES OF TEACHING ENGLISH BASED ON ICT - Eshankulova, Nigina (Журнал иностранных языков и лингвистики, 2021)
The processes of globalization and informatization, harmonization with the European system of higher education, laws and regulations of educational authorities require the improvement of methods of teaching a foreign language in the context of the use of ICT in universities. To accomplish this task, it is proposed to revise the teaching aids and pedagogical approaches that are used by teachers to teach a professionally oriented foreign language (ESP - English for Specific Purposes)